Maternal education and child stunting in Kenya: The role of socio-economic confounding using DHS 2022 data - Anastacia Katungo Maluki; Zerai Hagos; Kabiru Gulma; Michael Musili Nzau (Public Health and Occupational Safety Journal, 2026)
Background: Child stunting remains a major public health challenge in Kenya, reflecting long‑term nutritional deprivation and socioeconomic inequalities. Although maternal education is widely considered protective, its independent effect is often unclear due to confounding by structural factors. Objectives: To examine the association between maternal education and child stunting among children under five in Kenya and to assess the extent of confounding and effect modification by key sociodemographic factors. Methods: A cross‑sectional analytical study was conducted using data from the 2022 Kenya Demographic and Health Survey (KDHS). The sample included 19,530 children aged 0–59 months. Stunting was defined using height‑for‑age z-scores (<-2 SD). Descriptive, bivariate, stratified, and multivariable logistic regression analyses were performed, accounting for the complex survey design. Results: Stunting prevalence was 18.2%. Stunting decreased with increasing maternal education, from 21.4–21.7% among children of mothers with no or primary education to 8.7% among those with higher education (χ² = 238, p < 0.001). However, the association was weak (Cramer’s V = 0.117) and attenuated after adjustment for socioeconomic factors. Household wealth was the strongest predictor, with children in the richest households having significantly lower odds of stunting than those in the poorest households (AOR = 0.268; 95% CI: 0.222–0.323; p < 0.001). Stunting risk increased with age, particularly among children aged 6–23 months, while females had lower odds than males (OR = 0.717; 95% CI: 0.662–0.776). Stratified analyses showed stronger protective effects of maternal education among older children. In contrast, variation across wealth groups should be interpreted cautiously, given inconsistent and non-significant findings in some strata. No meaningful effect modification by child sex was identified. Conclusions: Child stunting in Kenya is primarily driven by structural socioeconomic factors. While maternal education is associated with reduced stunting, its effect is highly context dependent. Addressing poverty and inequality is essential for effective and equitable reductions in child stunting.